Relationship between Instructional Practices and Learning Practices with Students’ Achievement at Secondary Religious School in Selangor, Malaysia - Abdullah Omar, Siti Safariah (2009)
The main purpose of this study was to identify teachers’ instructional practices pertaining to delivery of teaching and evaluation of teaching of the four subjects namely Bahasa Melayu (BM), English (BI), Advanced Arabic (BAT) and Quranic and as-Sunnah (PAQAS) from the teachers’ and students’ perception. It also aims to identify teachers’ level of self-efficacy in their teaching, and to identify the students’ level of self-regulated learning and motivation in their learning. In addition, this study had examined the correlations between instructional practices from both the teachers’ and students’ perceptions, teachers’ self-efficacy level, students’ self-regulated learning and their level of motivation with students’ achievements in the respective subjects of BM, BI, BAT and PAQAS. The study was conducted at 20 Secondary Religious School in Selangor. It involved 80 Form Five teachers teaching the four respective subjects and 565 Form Five students. A set of questionnaires with likert-scale items and open-ended questions were used to collect information from the respondents. All data gathered were then analyzed with the use of SPSS (Statistics for the Social Sciences) computer program. The statistical analysis utilized both the descriptive and inferential statistics. The Descriptive statistics of frequencies, percentages, means and standard deviations were used to describe the research constructs. On the other hand, inferential statistics were used to obtain the correlations among the research constructs. Meanwhile the open-ended questions were used to get the additional information about students’ interest, problems faced by teachers, best teaching practices and teachers’ suggestions on improving the teaching quality of BM, BI, BAT and PAQAS. Findings of the study showed that the teachers’ perception of their teaching practices level were moderate: BM (2.86), BI (2.70), BAT (2.89) and PAQAS (2.65). The mean of teachers’ instructional practices in terms of teaching delivery from the students’ perception were also moderate: BM (2.51), BI (2.46), BAT (2.52) and PAQAS (2.46). This is based on rating scales of one to four. In general, with regard to instructional practices, the students’ perception was found lower than the teachers’ perception. The study also found that teachers’ instructional practices on evaluating of teaching from both the teachers’ and students’ perceptions were moderate. This is an exceptional for BAT teachers which showed a high level of teaching practice in terms of their evaluation of teaching mean of (3.09). Teachers’ self-efficacy which was based on rating scales from one to nine showed that the level was high for BM teachers (mean=7.21) and BAT teachers (mean= 7.11). On the other hand, the level was low for BI teachers (mean= 6.73) and PAQAS teachers (mean= 6.81). In relations to the students’ learning practices in terms of self- regulated learning, the study found that in general, the students’ self-regulated learning was moderate which a mean of 4.45, this was based on the rating scales from one to nine, meanwhile, the level of students’ motivation towards their studies was good (mean=5.44). Furthermore, the research findings also showed that from the students’ perception, there were significant correlations between the teaching practices of BM teachers and students’ achievements in terms of induction set (r = .12, p < .01), lesson delivery (r=.12 p < .01) and lesson closure (r = .17, p < .01). While for BI teachers, there were also significant correlations between students’ achievements and their instructional practices in terms of induction set (r = .19, p < .01), lesson delivery (r = .11, p < .01) and teaching approaches (r = .12, p < .01). Among the PAQAS teachers, it was found that the only significant correlation to the students’ achievement was in terms of induction set (r = .16, p < .01). On the teachers’ perceptions on instructional practices in terms of evaluation of teaching, BM teachers showed a significant correlation with students’ achievement with regard to follow-up action after the teaching (r = .61, p< .01). While based on students perception, BM teachers practices of evaluation of teaching was found significantly correlated to students’ achievement in evaluation technique (r = .18, p< .01) and follow-up action after the teaching (r = .12, p<.01). The findings also showed that the BAT teachers’ self-efficacy was significantly correlated to students’ achievement in terms of the lesson delivery (r = .68, p< .01), classroom management (r =.58, p < .01) and students’ involvement in their learning (r =.64, p < .01). Meanwhile, PAQAS teachers’ self-efficacy were found correlated significantly with students’ achievement in terms of their delivery of teaching (r = .57, p < .01) and students’ involvement in their learning (r = .50, p< .01). In conclusion the BM, BI, BAT and PAQAS teachers’ instructional practices in terms of delivery of teaching and evaluation based on the teachers’ and students’ perceptions were found moderate. While the level of teachers’ self-efficacy among BM and BAT teachers were found high. On the other hand, the level was low for BI and PAQAS teachers. Hence the BI and PAQAS teachers should be enhanced in their knowledge and skills regarding the instructional practices and their level of self-efficacy in order to help students to enhance their achievements. Meanwhile BM and BAT teachers need to improve their instructional practices hence given further training in teaching practices. Furthermore the students’ self-regulated learning was rather moderate, while the level of their motivation was high. Thus they need to be trained in time management and critical thinking effectively and also to develop a positive attitude towards learning. Based on the research findings several suggestions are put forward for future research.